Prospects for the Use of NGAL and KIM-1 for the Diagnosis of Acute Kidney Injury in Patients Receiving Antibacterial Therapy - E. Yu. Nikitin; V. N. Drozdov; M. A. Vyzhigina; O. A. Vorobieva; A. A. Astapovskiy; K. N. Khalaidzheva; E. V. Shikh (Вестник анестезиологии и реаниматологии)
The developers of Clinical Practice Guidelines for Acute Kidney Injury titled The Initiative to Improve Global Kidney Disease Outcomes (KDIGO) point at the need of new biomarkers for diagnosis acute kidney injury (AKI).The objective: to study and evaluate the diagnostic significance of the levels of neutrophil gelatinase-associated lipocalin (NGAL) and kidney injury molecule-1 (KIM-1) in patients with AKI in the early postoperative period when antibiotic therapy is used.Subjects and Methods. AKI frequency was assessed in 276 patients during the early postoperative period after the antibacterial drugs had been prescribed. Serum levels of KIM-1 and NGAL, glomerular filtration rate (GFR), creatinine, protein in urine were tested before the start of antibiotic therapy, in 24–48 hours, and in patients with AKI – additionally in 72–96 hours. The normal initial renal excretory function was registered only in 36 patients (13.04%). The majority of patients (242 patients, 86.96%) were diagnosed with chronic kidney disease of various stages.Results. NGAL and KIM-1 levels were higher in the group of patients with AKI before start of antibiotic therapy versus the group of patients with preserved renal function. However, a statistically significant increase in the level of KIM-1 and NGAL was found only in the group of patients with stages 3A and 3B of CKD versus the groups of patients with stages 1 and 2 of CKD. The second important observation is that a comorbid pathology in patients led to a high AKI incidence when antibiotic therapy was used – 35.86% (30–42%; 95%CI).Conclusion. The relationship of NGAL and KIM-1 levels with glomerular filtration rate (GFR) and KIM-1 level with the presence of proteinuria as indicators of impaired renal filtration function suggests that NGAL and KIM-1 levels reflect the state of renal filtration function. Based on this observation, it should be accepted that NGAL and KIM-1 levels can be used as markers for the diagnosis of AKI in patients receiving antibiotic therapy. The prescription of antibiotic therapy in the postoperative period in patients with surgical pathology and renal dysfunction leads to a high AKI incidence. Elevated KIM-1 and NGAL levels in AKI during the antibiotic therapy suggests their involvement in the reparation process.